Religiousness, Spirituality, and Salivary Cortisol in Breast Cancer Survivorship: A Pilot Study. Issue 2 (March 2018) - Hulett, Jennifer M.; Armer, Jane M.; Leary, Emily; Stewart, Bob R.; McDaniel, Roxanne; Smith, Kandis; Millspaugh, Rami; Millspaugh, Joshua
Abstract : Background: Psychoneuroimmunological theory suggests a physiological relationship exists between stress, psychosocial-behavioral factors, and neuroendocrine-immune outcomes; however, evidence has been limited. Objective: The primary aim of this pilot study was to determine feasibility and acceptability of a salivary cortisol self-collection protocol with a mail-back option for breast cancer survivors. A secondary aim was to examine relationships between religiousness/spirituality (R/S), perceptions of health, and diurnal salivary cortisol (DSC) as a proxy measure for neuroendocrine activity. Methods: This was an observational, cross-sectional study. Participants completed measures of R/S, perceptions of health, demographics, and DSC. Results: The sample was composed of female breast cancer survivors (n = 41). Self-collection of DSC using a mail-back option was feasible; validity of mailed salivary cortisol biospecimens was established. Positive spiritual beliefs were the only R/S variable associated with the peak cortisol awakening response ( r s = 0.34, P = .03). Poorer physical health was inversely associated with positive spiritual experiences and private religious practices. Poorer mental health was inversely associated with spiritual coping and negative spiritual experiences. Conclusions: Feasibility, validity, and acceptability of self-collected SDC biospecimens with an optional mail-back protocol (at moderate temperatures) were demonstrated. Positive spiritual beliefs were associated with neuroendocrine-mediated peak cortisol awakening response activity; however, additional research is recommended. Implications for Practice: Objective measures of DSC sampling that include enough collection time points to assess DSC parameters would increase the rigor of future DSC measurement. Breast cancer survivors may benefit from nursing care that includes spiritual assessment and therapeutic conversations that support positive spiritual beliefs.